Long-term psychological distress in breast cancer survivors and their matched controls: A cross-sectional study. (December 2019) - Maass, S.W.M.C.; Boerman, L.M.; Verhaak, P.F.M.; Du, J.; de Bock, G.H.; Berendsen, A.J.
Highlights: In our study, a large proportion of breast cancer survivors did not experience symptoms of depression or anxiety. Long-term BC survivors are at increased odds of (severe) symptoms of depression and severe symptoms of anxiety. The increased risks are independent of a history of depression or of use of antidepressants. The increased risks are independent of time since breast cancer diagnosis. The increased risks seem to persist for at least 10 years after breast cancer diagnosis. Abstract: Introduction: Breast cancer survivors often experience psychological distress shortly after diagnosis. Long-term psychological effects, however, have not been clearly demonstrated. Methods: This cross-sectional cohort study included 350 breast cancer survivors and 350 age-matched and general-practitioner-matched women. The median follow-up was 10 years. Using logistic regression we compared breast cancer survivors with controls on having (severe) symptoms of depression and/or anxiety, as measured with the Hospital Anxiety and Depression Scale. In multivariable logistic regression, we adjusted the results for a history of depression or prescription of antidepressants. Results: Larger proportions of breast cancer survivors experienced symptoms of depression (10.6%) compared with controls (4.9%) and symptoms of anxiety (18.6%) compared with controls (16.3%). The odds of symptoms of depression (OR 2.3, 95%CI 1.3–4.2), severe symptoms of depression (OR 3.3, 95%CI 1.1–10.3) and severe symptoms of anxiety (OR 2.1, 95%CI, 1.1–4.0) were significantly higher for breast cancer survivors than for controls, even after adjusting for history of depression or prescription of antidepressants. No significant difference was seen for mild symptoms of anxiety. Conclusions: Breast cancer survivors have an increased risk of symptoms of depression, including severe symptoms, and severe symptoms of anxiety compared with controls, for up to at least 10 years after diagnosis.